Integrative Learning in History Education: A Systematic Literature Review - Atqo Akmal (Dinamika Ilmu, 2022)
In general, history is a construction of the past that should use models, methods, and concepts of other social sciences to explain the changes or events throughout human life and civilization. Thus, the assumption that history should be explained from a broader perspective of social sciences and the deep analysis of social theory has transformed the need for an interdisciplinary approach in history education. In the quest for an advanced learning approach to history education, this article proposes integrative learning as an approach that could meet the need for the integration of various perspectives and theories from social science disciplines in learning history. Constructively explained through a systematic literature review of related studies oriented towards history, interdisciplinary, multidisciplinary, and integrative learning, this article works on the possibility of integration encompassing four steps, namely establishing a purpose, understanding and leveraging disciplinary insights, leveraging integration, and critical stance. Despite the lack of empirical research, integrative learning is a promising concept that could improve the method of fostering high-order thinking skills in history education.